Role of aspirin in cancer prevention - Meng Sun; Jun Yu; Jie Wan; Xiaoyun Dou; Xiaoying Chen; Fang Ye (Cancer Treatment and Research Communications)
Aspirin [1], also known as acetylsalicylic acid, is a common non-steroidal anti-inflammatory drug (NSAID). The available evidence shows that aspirin can effectively prevent and treat diseases such as rectal, gastric, ovarian, prostate, and lung cancer. Aspirin has been extensively studied for the prevention and treatment of colorectal cancer. In recent years, studies have found that the potential mechanism of aspirin in the prevention and treatment of cancer may lie in immune regulation, the role of DNA repair pathways, the regulation of cell metabolism, anti-inflammatory effects and antiplatelet effects.